"Composable BPM: Modularizing Workflows for Agility and Efficiency" (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2017)
Composable Business Process Management (BPM) architecture represents a significant evolution in process design, introducing modularity and adaptability to business workflows. By enabling organizations to break down complex business processes into smaller, reusable components, composable BPM offers a high level of agility, allowing businesses to reconfigure workflows quickly in response to changing market demands. This research explores how Pega, a leading BPM platform, has facilitated composable processes for businesses, empowering them to streamline operations, improve efficiency, and enhance flexibility. Through a review of case studies and industry reports, this article highlights the benefits and challenges associated with adopting composable BPM architecture, particularly in fast-paced industries such as finance, insurance, and retail. The research also examines how modular BPM components, such as case management, task automation, and decision services, can be orchestrated to create agile, scalable workflows. This article provides insights into how composable BPM can help organizations drive innovation, increase process efficiency, and achieve greater responsiveness to market dynamics. Ultimately, composable BPM architecture is poised to transform how businesses design and execute workflows, enabling them to stay competitive in a rapidly evolving business environment.